PATOGENESIS HAWAR DAUN BIBIT PINUS MERKUSII YANG DISEBABKAN OLEH PESTALOTIA THEAE DI PESEMAIAN - ., Sutarman; Hadi, Soetrisno; Suryani, Ani; ., Achmad; Saefuddin, Asep (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2004)
Pathogenesis of Needle Blight of Pinus merkusii Seedlings Incited by Pestalotia theae in The Nunery. The objectives of theiudy were to clarify the mechanism by which Pestalotia theae  incites the disease and the defense mechanism of the pine seedling  against the attack by the pathogen. The germination tube,2.9 µm in diameter, produced by the germinating conidiospore penetrated the leaf cells via the stomata, which were wider in diameter. The pathogen was able to produce pectinolytic and cellulolytic enzymes required for the degrading of the host cell wall components. The epidermis was covered-by a thick cuticulae layer. The activity of the peroxidase reduced in the cotyledon, the primary leaf and in the secondary leaf decreased, when the seedlings were 1-2,2-3, and >3 month old.